Identification of loci for single/double flower trait by combining genome‐wide association analysis and bulked segregant analysis in peach (Prunus persica). (13th March 2019) - Meng, Ge; Zhu, Gengrui; Fang, Weichao; Chen, Changwen; Wang, Xinwei; Wang, Lirong; Cao, Ke
Abstract: Background: Peach is a typical perennial fruit crop that can be categorized both as an ornamental and edible crop. Double flower is an important appearance trait, in which breeders are pursuing in high‐quality ornamental peach breeding. The single/double flower character in peach is controlled by one gene,   Dl, and the underlying genetic mechanism is unknown. Objective: In this study, we explored the genetic basis of single/double flower trait in peach in a genome‐wide association study using 1 042 687 SNPs characterized in 201 accessions. Methodology: Four loci were identified to be significantly associated with the trait on chromosomes (Chr.) 1, 2 and 6. Besides, the bulked segregant analysis (BSA) was performed with two DNA bulks (single and double flower pool) from the F1 population plants of a cross 'Juhuatao' × 'Honggengansutao'. Results: We found a genomic region on Chr. 2 by the BSA, which overlapped the association peak on Chr. 2 in the GWAS—denoted as a region harbouring Dl . Finally, a candidate gene was identified by expression analysis of different plant tissues. Conclusion: Our results provide insights into the genetic basis of flower shape and might facilitate marker‐assisted selection breeding for ornamental peach.